Zr-substituted Ba0.6Sr0.4TiO3 ferroelectric thin films grown by pulsed laser deposition (PLD) at different laser fluence. (18th August 2017) - Goud, J. Pundareekam; Sandeep, Kongbrailatpam; Emani, Sivanagi Reddy; Alkathy, Mahmoud. S.; Naidu, Kuna Lakshun; Raju, K. C. James
ABSTRACT: Zr-substituted Ba0.6 Sr0.4 TiO3 ((Ba0.6 Sr0.4 )(Ti0.8 Zr0.2 )O3 ) - BSZT) thin films are deposited by using Pulsed Laser Deposition method with different fluence at optimized conditions on amorphous fused silica substrates. The X-ray diffraction (XRD) pattern of the films confirms the formation of cubic phase. Raman studies are performed to understand vibrational modes present in the films. The optical band gap of deposited BSZT thin films were calculated from the transmittance measurements. Microwave dielectric properties of the thin films deposited at 2 J/cm 2 were measured. These results show BSZT thin films are useful in tunable microwave devices.